Design and simulation of MEMS microvalves for silicon photonic biosensor chip. (20th March 2018) - Amemiya, Yoshiteru; Nakashima, Yuuto; Maeda, Jun; Yokoyama, Shin
Abstract: For the early and easy diagnosis of diseases, we have proposed a silicon photonic biosensor chip with two kinds of MEMS microvalves for a multiple-item detection system. The driving voltage of the vertical type with the circular-plate capacitor structure and that of the lateral type with the comb-shaped electrode are investigated. From mechanical calculations, the driving voltage of the vertical type is estimated to be 30 V and that of the lateral type to be 15 V. The propagation loss at the intersecting waveguides of arrayed ring-resonator biosensors is also estimated. In the case of optimized intersecting waveguides, more than 67% transmittance of TE-mode light is simulated for the series connection of 20 intersecting waveguides. It is confirmed that it is possible to fabricate an 8 × 12 arrayed biosensor chip in an area of 1 × 1.5 mm 2 taking the device size of the microvalves into consideration. We have, for the first time, designed a whole system, including sensors and a fluid channel with MEMS microvalves.